Indirect procedures: a musician's guide to the Alexander Technique - Alcantara, Pedro De (Oxford Clarendon Press, 1997)
Written by an experienced professional musician and teacher of the Alexander Technique, this volume is the first to deal specifically with the application of the Technique to music-making. Introducing the musician to the principles and procedures evolved by F. M. Alexander (1869-1955), the book contains practical advice related to all areas of musical activity, from technique, sound production, and interpretation, to daily practice, rehearsal routines, and the mitigating of stage fright and health problems.